Research advances in the relationship between renal metabolism and hypertension - Jian Liu; Xiao-liang Zhang (Editorial Department of Journal of Clinical Nephrology, 2023)
Hypertension has remained a heavy disease burden in the world. As an important organ with high specific generation rate, regulating water and sodium balance and partial hormone secretion, kidney has always played some vital roles in the regulation of blood pressure. This review summarized the relationship between kidney energy, substrate metabolism and hypertension and examined the relationship between renal energy metabolism abnormalities due to altered genetic factors related to mitochondria and blood pressure. Moreover, physiological and molecular mechanisms of hypertension caused by the changes of renal material metabolism through affecting the balance of water and sodium and the regulation of renin and other hormones were discussed from the perspectives of animal and human experiments, providing references for accurate prevention and precise treatment of hypertension in the future.